Student Excellency Database System - Tiu, Yan Lin; Abd Wahab, Alawiyah (Multidisciplinary Applied Research and Innovation, 2021)
Nowadays, the web-based system such as Database Management System or known as DBMS are widely use in every sector. With the existence d this system, the aim of increasing decision-making and organizational performance of a company will be realized. Currently, HEP still depends on manual processes and suggestions from the club’s advisor in selecting students for a competition. The staff will select those who are potentially eligible based on the information that they already on hand such as the data that retrieved from google form. This circumstance poses a serious difficulty for HEP, namely, the limited number of potential students who can compete on behalf of the university in a competition. A Student Excellency Database System were designed and overall get the good result at the stage of field testing.